Pendidikan Remaja: Tela’ah tentang Model Pembelajaran Moral Keagamaan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
: Adolescent is community which often become the device of pride and yearn, but at the same time target from systematic evil plan. Therefore, improving quality, creativity, and credibility is something that must to do. Key factor from that all is religious morality. Education represents the most appropriate institution to construct and take care of the adolescent existence and their morality. Anyway, see the adolescent characteristic and its specific challenge; education and learning have to come up in correct perform. Here approach and learning model will give significant contribution to successfulness of religion study.